Goal-directed fluid therapy in autologous breast reconstruction results in less fluid and more vasopressor administration without outcome compromise. Issue 9 (September 2021) - Polanco, Thais O.; Shamsunder, Meghana G.; Hicks, Madeleine E.V.; Seier, Kenneth P.; Tan, Kay See; Oskar, Sabine; Dayan, Joseph H.; Disa, Joseph J.; Mehrara, Babak J.; Allen, Robert J.; Nelson, Jonas A.; Afonso, Anoushka M.
Summary: Objective: Aggressive or restricted perioperative fluid management has been shown to increase complications in patients undergoing microsurgery. Goal-directed fluid therapy (GDFT) aims to administer fluid, vasoactive agents, and inotropes according to each patient's hemodynamic indices. This study assesses GDFT impact on perioperative outcomes of autologous breast reconstruction (ABR) patients, as there remains a gap in management understanding. We hypothesize that GDFT will have lower fluid administration and equivocal outcomes compared to patients not on GDFT. Methods: A single-center retrospective review was conducted on ABR patients from January 2010-April 2017. An enhanced recovery after surgery (ERAS) using GDFT was implemented in April 2015. With GDFT, patients were administered intraoperative fluids and vasoactive agents according to hemodynamic indices. Patients prior to April 2015 were included in the pre-ERAS cohort. Primary outcomes included the amount and rate of fluid delivery, urine output (UOP), vasopressor administration, major (i.e., flap failure) and minor (i.e., seroma) complications, and length of stay (LOS). Results: Overall, 777 patients underwent ABR (ERAS: 312 and pre-ERAS: 465). ERAS patients received significantly less total fluid volume (ERAS median: 3750 mL [IQR: 3000–4500 mL]; pre-ERAS median: 5000 mL [IQR 4000–6400 mL]; and p <0.001), had lower UOP, were more likely to receive vasopressor agents (47% vs 35% and p <0.001), and had lower LOS (ERAS: 4 days [4–5]; pre-ERAS: 5 [4–6]; and p <0.001) as compared to pre-ERAS patients. Complications did not differ between cohorts. Conclusions: GDFT, as part of ERAS, and the prudent use of vasopressors were found to be safe and did not increase morbidity in ABR patients. GDFT provides individualized perioperative care to the ABR patient.